Proceedings of the 1st International Conference on Information and Communication Technologies for Ageing Well and E-Health 2015
DOI: 10.5220/0005449001060117
|View full text |Cite
|
Sign up to set email alerts
|

On Modeling the Cardiovascular System and Predicting the Human Heart Rate under Strain

Abstract: With the increasing average age of the population in many developed countries, afflictions like cardiovascular diseases have also increased. Exercising has a proven therapeutic effect on the cardiovascular system and can counteract this development. To avoid overstrain, determining an optimal training dose is crucial. In previous research, heart rate has been shown to be a good measure for cardiovascular behavior. Hence, prediction of the heart rate from work load information is an essential part in models use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Adjustment of short term prediction models for the usage of session prediction is mathematically possible, but can lead to a lack of accuracy as shown in Ludwig et al ( 2015 ) and Hoffmann and Wiemeyer ( 2017a ). If a short term prediction model makes use of previous HR values, respective previously computed HR values could be used in the corresponding session prediction model.…”
Section: Modeling and Prediction Of Heart Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Adjustment of short term prediction models for the usage of session prediction is mathematically possible, but can lead to a lack of accuracy as shown in Ludwig et al ( 2015 ) and Hoffmann and Wiemeyer ( 2017a ). If a short term prediction model makes use of previous HR values, respective previously computed HR values could be used in the corresponding session prediction model.…”
Section: Modeling and Prediction Of Heart Ratementioning
confidence: 99%
“…Particularly interpretability of a model's parameters is favorable in HR prediction: to model not artifacts but real factors influencing the HR significantly improves the accuracy of prediction. Ludwig et al ( 2015 ) gives a comparison of different types of phenomenological models and presents their accuracy in approximation and prediction of different time horizons of HR. The results illustrate that good accuracy in approximation or prediction of few seconds does not transfer to prediction accuracy in session prediction.…”
Section: Modeling and Prediction Of Heart Ratementioning
confidence: 99%
See 1 more Smart Citation
“…In the medical field, this study builds upon a fast-expanding literature that applies machine learning tools in health and healthcare forecasting. For example, the risk of the onset of a disease, whether it be cardiovascular [ 26 , 27 ] or not [ 28 ]; hospital discharge volume [ 29 ]; arrhythmia prevention [ 30 ], response to training in healthy individuals [ 31 ] or in individuals with pathologies [ 32 ]; identification of the existence of heart diseases [ 33 ]; or evaluation of the risk of mortality in subjects who had a heart attack during the previous year [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Informative data on changes in HRV were obtained in the analysis of recovery processes in the body after performing physical activity of varying intensity [9,10,11]. A number of studies in which the intensity of physical activity was selected based on the changes in the HRV indices allowed to prove the effectiveness of this approach from the point of view of the development of the level of training [12,13]. Other studies [14] have shown that HRV changes in accordance with maximum absorption of oxygen and lactic acid levels.…”
Section: Introductionmentioning
confidence: 99%